Strategy for Improving Quality of Service in Management of Library in Tadulako University - Prita Andarbeni; Iwan Satibi; Ummu Salamah (GoAcademica Research & Publishing, 2019)
The main problem in research is that the quality of library management services at the University of Tadulako is not yet optimal. This study aims to study and analyze the library service quality strategy carried out by library officials at Tadulako University. This research was conducted using a mixed method, through two approaches namely quantitative and qualitative (mix method). The data collection is done through questionnaires, participant observation, and interviews. The results of the study found that the quality of library services is largely determined by the completeness of facilities and infrastructure, reliability, responsiveness of officers, the ease of service processes and security guarantees while in the library building. This study concludes that in order to improve the quality of library services, it is needed a strategy to improve the quality of services based on information technology (IT). The strategy that needs to be done to improve the quality of library services is the service diversification strategy, which is a strategy that focuses on optimizing the use of force to reduce threats.